Unilateral Measles-Associated Retrobulbar Optic Neuritis without Encephalitis: A Case Report and Literature Review - Hirayama, Takehisa (S. Karger AG, 2010)
Optic neuritis (ON) is a rare neurological complication of measles infection. Little is known about measles-associated retrobulbar ON. Here, we report a distinct patient with unilateral retrobulbar ON due to measles infection. A 26-year-old woman developed maculopapular rash and Koplik spots. On the following 3 days, she noticed blurred vision in the left eye. A Goldmann visual field test showed inferior nasal quadrantanopsia in the left eye. Visual acuity was 20/20 in OD and 20/100 in OS. Pupillary size was 2.0 mm in the right eye and 4.0 mm in the left eye. Light reflexes were slightly sluggish in the left eye. Ophthalmoscopy showed mild pallor of the left optic disc. Central critical flicker fusion frequency (CFF) was 40.7 Hz in the right eye and 10.1 Hz in the left eye (normal =29.0). Visual evoked potentials showed that P100 latencies were delayed on the left side (133 ms). Brain and spinal cord MRI was normal. Orbital MRI displayed abnormal enhancement in the left optic nerve. Serum and cerebrospinal fluid IgG titers of anti-measles antibodies were increased. Left measles-associated ON was diagnosed. Methylprednisolone pulse therapy followed by oral administration of prednisolone ameliorated visual acuity, visual field and CFF. The neuroophthalmic profile of our patient indicated that measles infection triggered isolated retrobulbar ON, leading to unusual visual deficits. Thus, physicians should pay more attention to variable patterns of measles-associated ON.